MicroRNA-21-5p from induced pluripotent stem cells promotes neuroprotection of retinal ganglion cells in optic nerve crush model - Qing Xia; Wei Chen; Jiawei Xiong; Xiaofen Mo (BMC Ophthalmology)
Abstract Introduction Retinal ganglion cells (RGCs) are susceptible to degenerative conditions such as glaucoma and traumatic optic neuropathies, which lead to vision loss. MicroRNA-21-5p has demonstrated potential neuroprotective effects, but its mechanisms in optic nerve injury remain underexplored. This study evaluates the neuroprotective role of microRNA-21-5p derived from induced pluripotent stem cells (iPSCs) in an optic nerve crush (ONC) model. Materials and methods In vitro qPCR demonstrated that the expression of microRNA-21-5p was increased in the co-culture medium of RGCs and iPSCs. Subsequently, in the in vivo experiments, we used a microRNA-21-5p agonist to assess its protective effects on RGCs. RNA sequencing was then performed in a mouse ONC model after treatment with a microRNA-21-5p agonist to explore the mechanisms underlying its neuroprotective effects on RGCs. Results As demonstrated in our previous experiments, the RGCs-iPSCs co-culture group led to a higher survival rate of RGCs, as indicated by live/dead cell staining, compared to the RGCs-only group. Quantitative PCR (qPCR) results revealed a significant increase in the expression of microRNA-21-5p in the medium of the RGCs-iPSCs co-culture group. Furthermore, the survival rate of mouse retinal RGCs treated with a microRNA-21-5p agonist was significantly greater than that of the control group. Lastly, RNA sequencing of the retina from microRNA-21-5p agonist-treated mice indicated that microRNA-21-5p plays a protective role in RGCs by downregulating the expression of several genes, including Irf1, Ccl4, Itk, Cxcr2, Dclre1c, Traf1, Traf2, Rbl1, Cxcl5, Cxcl3, Cxcl1, Cxcl9, Il2rg, Cd3e, Cd3d, Cxcl10, Ccl5, Ccl12, Tap1, and Cxcr4. Conclusion MicroRNA-21-5p derived from iPSCs can enhance the survival rate of RGCs in the ONC model. This suggests that microRNA-21-5p may represent a novel and effective strategy for repairing RGC damage. Such a strategy could potentially be realized through the modulation of apoptosis, T-cell regulatory pathways, or TNF-α signaling.